(untitled) (Siddhajyoti Interdisciplinary Journal, 2023)
Representation of cultural aspects in the textbook has become a prominent issue in the present context and it is also important for a multicultural country like Nepal. This paper explores cultural representations of the socio-culturally diverse groups of people in Nepal with reference to the Grade Nine English textbook published by the Curriculum Development Center and its implication by analyzing the content of the textbook. The information was collected through the Grade Nine English textbook, and in-depth interviews selecting two textbook authors using convenient sampling procedure and four Grade Nine students using purposive sampling procedure. The information was interpreted and discussed categorizing them into three themes: inclusion of cultural heterogeneity, typicality and organic cultural identity, and cultural tolerance. The study reveals that the Grade Nine English textbook seems to be inclusive and has tried to address the socio-culturally diverse groups of people in Nepal. This inclusiveness is essential for the cognitive and academic engagement of the culturally-diverse groups of students.